2013
DOI: 10.1371/journal.pone.0053163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Catchment and Riparian Landscape Setting on Water Chemistry and Seasonal Evolution of Water Quality in the Upper Han River Basin, China

Abstract: Six-year (2005–2010) evolution of water chemistry (Cl−, NO3 −, SO4 2−, HCO3 −, Na+, K+, Ca2+ and Mg2+) and their interactions with morphological properties (i.e., slope and area), land cover, and hydrological seasonality were examined to identify controlling factors and processes governing patterns of stream water quality in the upper Han River, China. Correlation analysis and stepwise multiple regression models revealed significant correlations between ions (i.e., Cl−, SO4 2−, Na+ and K+) and land cover (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…TN, DN, NO 3 − -N, TP and DP were higher in the lower part of the basin where more land has been developed and were lower in the upper-eastern part of the Cao-E River basin. Turbidity and EC were higher in the lower part of the basin ( Figure 2 ) where the reach is often affected by tides and/or point source pollution [36], [37].…”
Section: Resultsmentioning
confidence: 99%
“…TN, DN, NO 3 − -N, TP and DP were higher in the lower part of the basin where more land has been developed and were lower in the upper-eastern part of the Cao-E River basin. Turbidity and EC were higher in the lower part of the basin ( Figure 2 ) where the reach is often affected by tides and/or point source pollution [36], [37].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have highlighted land use/landscape within different buffer zones scales. These studies conclude that changes in the spatial characteristics of landscape patterns are a leading factor impacting water quality deterioration [32,34,38,39], the extent and scale of which are case-specific. Research also indicates there is a substantial relationship between precipitation and water quality, as precipitation and surface runoff exert significant impact on flow rates and concentration of contaminants in stream water.…”
Section: Introductionmentioning
confidence: 87%
“…Such variations are seasonal [1,33,34,40]. Li et al found that riparian land use exerted the largest influence on the upper Han River basin of China during the dry season [39]. However, Shen et al found that landscape characteristics had a strong correlation with water quality during the rainy season [26,31].…”
Section: Introductionmentioning
confidence: 99%
“…The mean elevation of sub-watershed follows the literature while the mean slope gives opposite results. The impact of mean slope on water chemistry varies due to the physical characteristics of the sub-watershed, which includes surficial geology, land use, morphological variables and surficial debris [51,52].…”
Section: Effects Of Topographic Factors On Precipitation Elasticitymentioning
confidence: 99%